2022
DOI: 10.3390/nu14224904
|View full text |Cite
|
Sign up to set email alerts
|

A Snapshot of the Experience of Dietitians during the COVID-19 Crisis in Five Arab Countries: Findings from a Regional Cross-Sectional Study

Abstract: COVID-19’s intimidating spread has challenged the resilience of the global health systems, causing shifts in the practices of healthcare workers, including dietitians. The current study aimed to assess the change in dietitians’ practices and duties in hospitals/clinics after the commencement of COVID-19 pandemic. This cross-sectional study was conducted in five Arab countries between November 2020 and January 2021. A convenient sample of 903 dietitians filled an online self-administered questionnaire to meet t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In closing, institutions must provide a welcoming and favorable environment for dietitians to practice their profession remotely, with the greatest possible benefits and the fewest possible withdrawals. Moreover, dietitians shouldered new responsibilities in responding to nutrition myths during the pandemic period (7). This is demonstrated by the results of the current study, which found that during the pandemic, there was a marked increase in the number of dietitians who reported responding to nutrition myths on social media.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…In closing, institutions must provide a welcoming and favorable environment for dietitians to practice their profession remotely, with the greatest possible benefits and the fewest possible withdrawals. Moreover, dietitians shouldered new responsibilities in responding to nutrition myths during the pandemic period (7). This is demonstrated by the results of the current study, which found that during the pandemic, there was a marked increase in the number of dietitians who reported responding to nutrition myths on social media.…”
Section: Discussionmentioning
confidence: 55%
“…As for dietitians, "telenutrition, " defined by the American Dietetic Association (ADA), is a subset of telehealth that "involves the interactive use of electronic information and telecommunications technology to implement the nutrition care process (NCP) with remote patients or clients. " (6) In this regard, our earlier survey in five Arab countries found that, during the COVID-19 pandemic, the Arab hospital dietitian's responsibilities extended beyond the nutrition care setting to include educating the public, answering questions, fostering positive changes in eating habits and teaching them how to do it by disseminating accurate information about nutrition and dispelling myths about it (7). In addition, Arab dietitians developed individualized nutrition plans, offered nutrition support to COVID-19 patients, managed the nutrition-related symptoms of the coronavirus, and prevented the disease's metabolic complications (7), which are typically linked to obesity, cardiovascular disease, and diabetes (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation